Development of ethnoscience-based student worksheets of redox reactions, volta cells, and corrosion using liveworksheets - Liana Vinca Rosea Cristy; Fransisca Ditawati Nur Pamenang (Pascasarjana Universitas Negeri Medan, 2023)
Learning about ethnoscience can help students better understand chemistry because it connects to their daily experiences. However, students often struggle with redox and electrochemical concepts due to a lack of appropriate learning materials and difficulty grasping these ideas. This research aims to achieve the following objectives: (1) develop ethnoscience-based student worksheets on redox reactions, Volta cells, and corrosion using Liveworksheets, following the 4D development model modified to 3D; (2) create ethnoscience-based student worksheets on these topics that are valid, effective, and practical. The research employed validation sheets and questionnaires as instruments, with a sample of six students from the 12th grade. Data was analyzed descriptively. The results indicate that (1) the modified 4D development model was suitable for creating the student worksheets due to its systematic stages and adaptability to researchers' needs; (2) both the media and material showed high validity percentages, averaging 88% and 89%, respectively. The worksheets were considered quite effective, with an average percentage of 66%, and practical, with an average percentage of 78%. Overall, the developed product can be effectively used to teach redox reactions, voltaic cells, and corrosion in chemistry using Liveworksheets.Keywords: Corrosion; Ethnoscience; Redox reaction; Students’ worksheets; Voltaic cell